Elevated CD4⁺/CD8⁺ ratio and D-dimer as diagnostic biomarkers for Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis versus infectious mononucleosis in children: a retrospective case-control study - Yun Cheng; Wenjia Tong; Wangqiang Li; Yuanyuan Duan; Jingjing Jin; Biquan Chen (BMC Infectious Diseases)
Abstract Objective To identify potential diagnostic biomarkers distinguishing Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) from infectious mononucleosis (EBV-IM) in pediatric patients using a retrospective case-control design. Methods This study enrolled a total of 160 pediatric patients, including 132 with Epstein-Barr virus-associated infectious mononucleosis (EBV-IM) and 28 with EBV-associated hemophagocytic lymphohistiocytosis (EBV-HLH). Serum levels of CD4⁺ T cells, CD8⁺ T cells, and D-dimer were quantified by flow cytometry and immunoturbidimetry, respectively. The CD4⁺/CD8⁺ ratio was calculated from absolute counts. These parameters, along with clinical and laboratory features, were compared between the EBV-IM and EBV-HLH groups. Binary logistic regression was used to analyze the risk factors for the progression of EBV infection to EBV-HLH. The clinical value of CD4⁺/CD8⁺ ratio and D-dimer levels in diagnosing EBV-HLH was assessed using receiver operating characteristic (ROC) curve analysis. Results The average age of the EBV-HLH group was significantly lower than that of the IM group (p < 0.05). The EBV-HLH group had significantly higher levels of NLR(Neutrophil to Lymphocyte Ratio), PLR(Platelet to Lymphocyte Ratio), D-dimer, EBV-DNA, disease duration, CD4⁺/CD8⁺ ratio, and AST/ALT compared to the IM group (p < 0.05).Binary logistic regression analysis indicated that a higher CD4⁺/CD8⁺ ratio (OR = 17.60, 95% CI: 1.89–163.64; p < 0.05) and elevated D-dimer levels (OR = 1.31 per 1 mg/L increase, 95% CI: 1.08–1.59; p < 0.05) were significantly associated with EBV-HLH. Building upon the identified associations, we evaluated the diagnostic performance of these biomarkers. ROC curve analysis demonstrated that CD4⁺/CD8⁺ ratio > 0.455 (Youden index = 0.638, sensitivity = 92.4%, specificity = 71.4%) and D-dimer > 1.675 mg/L (Youden index = 0.683, sensitivity = 82.6%, specificity = 85.7%) optimally discriminated EBV-HLH from EBV-IM. The combined model significantly enhanced diagnostic accuracy (Youden index = 0.811), with AUC values of 0.837 (95%CI: 0.76–0.91), 0.869 (95%CI: 0.80–0.94), and 0.962 (95%CI: 0.935–0.989) for CD4⁺/CD8⁺ ratio, D-dimer, and their combination, respectively. Conclusion Elevated CD4⁺/CD8⁺ ratio and D-dimer serve as potential diagnostic biomarkers for pediatric EBV-HLH. Their combined detection enhances differentiation from EBV-IM, though validation through prospective studies is warranted.